Exploring Repeat Substance Abuse in Female Offenders: A Phenomenological Study - Shar Ainie A Serapion (Advanced Qualitative Research, 2024)
Substance abuse relapse contributes to the Philippines' ongoing problem. Stigmatization and a lack of appropriate aftercare services impede the development of crucial skills for successful reintegration into society. To address the essential issue of relapse from substance addiction, this study seeks to provide information specific to the issues that lead to repeat substance abuse in female offenders. The nation's rising relapse rates and the serious implications of their acts highlight the importance of this study. To prevent relapse and enhance rehabilitation, it is critical to identify and address the underlying causes. Utilizing Interpretative Phenomenological Analysis (IPA), eight (8) repeat substance abuse female offenders ages 38-53 years old who were jailed twice for substance abuse in Calamba City, Laguna, Philippines, were asked using a semi-structured interview. This study generated ten (10) themes which were: Longing for Loved Ones, Strict Protocols, Difficult Tasks, and Unappetizing Foods; Therapeutic Programs; Mixed Emotions, Family Reintegration, Working Habits; Negative Labeling, Insufficient Support from Family and/or Peers; Physical and Mental Well-Being; Livelihood and Socialization; Positivity and Resilience; Dealing with Relapse; Family Problem and Acquaintances; and Lack of Psychological Support. Consequently, an improved diversion program was created to help prevent the relapse of female drug re-offenders after being released from jail.